(3NhGU GdCOhjI GdeaQOIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s ((3MfXdI Hf YHO Gddg , YJjb GdTjN GdCejQ hdi GdOjf CHj GdaVd jMj Hf GdebdO Hf SdWGf Hf RdjN s)
(3ChdgG (B:s
(3GdMGOg , Cajhf , bGd LGdjfhS Gfg HGQO ai GdOQLI GdQGYHI HHQO GdCYVGA GdTOjOI GdMS hjfJaY ef GdOHMI s
(3BNQgG (B:s
(3jGbhJ (B: (3CLhOg GdCMeQ GdQeGfi , hbjd Cfg jefY ef LehO GdOe EPG Ydb Ydi GdEfSGf s
(3jfbU (B26 (3hQbI ef GdChds
(3hjHpOC HeGOI GdCajhfs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
Keywords: (3GdWHs